Depressive disorders as a cause of incapacity to consent marriage - LESZCZYŃSKI, GRZEGORZ (Prawo Kanoniczne, 2017)
Taking up the issue of depresion as a cause for declaring a marriage null and voit, the author begins his reections with a look at psychosis. From the point of view of marriage validity, of special signicance is also the analysis of depresion with very particular medical aspects. e cause of nullity of a marriage discussed here, in turn, requires a rather precise denition of depresion and the factors by which it may be triggered. e last part of the author’s reections is devoted to the analysis of canon 1095 of the Code of Canon Law, especially to the denition of cases when this depresion is serious enough to exclude marriage validity.